KEANEKARAGAMAN KANTONG SEMAR (Nepenthes spp) PADA SEMAK BELUKAR DAN AREAL TERBUKA DI KEBUN RAYA SAMBAS KABUPATEN SAMBAS KALIMANTAN BARAT - Yuniarty, Rinny; Dewantara, Iswan; Herawatiningsih, Ratna (JURNAL HUTAN LESTARI, 2020)
Sambas Botanical Garden is a conservation forest area that has a high diversity of flora and one of them is the Kantong Semar (Nepenthes spp). Research aims; (1) conducting a study of the species diversity of Kantong Semar (Nepenthes spp) in shrubs and open areas in the Sambas Botanical Garden, (2) Study to changes in the composition of Kantong Semar species (Nepenthes spp) in Sambas Botanical Garden, (3) determining species composition and dominant of kantong semar (Nepenthes spp) that grows in shrubs and open areas. This research was conducted by a survey method in which the laying of observation plots by purposive sampling. The results of the study showed that the species diversity of Kantong Semar (Nepenthes spp) in the Sambas Botanical Garden was a low category with a value of 0.254 in shrubs and an open area of 0.01756. There was a change in the composition of the Kantong Semar species after two years of previous research. The change occurred where two new species of N. xneglecta and N.gracilis Korth that grown in Sambas Botanical Garden. Based on the results of morphological analysis, we found as many as 5 species of Kantong Semar consisting of N. mirabilis (Lour) Druce, N.gracilis Korth, N.ampullaria Jack, N. xneglecta, N. xhookeriana, which grow in shrubs, and N. mirabilis (Lour) in open area. The results of the analysis of the Importance Value Index (INP) that dominant species are N.ampullaria Jack with a value of 107.02 and N. xhookeriana 33.32 where both species of Kantong Semar grown in the shrub area.Keywords: Kantong semar (Nepenthes spp), shrubs and open area, Species diversity.